Integration of Solar-Powered Drip Irrigation and Controlled Deficit to Increase Productivity and Water Efficiency of Red Chili Peppers in Alfisol Drylands - Nainggolan, Jekli Boy (Cattleya Darmaya Fortuna, 2025)
Uncertain water availability is a major constraint to red chili cultivation on dry land with Alfisol texture. This study evaluated the performance of solar-powered drip irrigation (SPDI) combined with regulated deficit irrigation (RDI) and organic mulch on yield, water use efficiency (WUE, kg m⁻³), fruit quality, and financial feasibility. A three-factor randomized block design (single dry season) was used: irrigation rate 100% ETc (I100), 80% ETc (I80), 60% ETc (I60) × mulch without mulch (M0) vs straw mulch 5 t ha⁻¹ (M1) × SPDI program (continuous day) vs scheduled SPDI (split, morning–evening); 3 replications; plots 6 × 10 m (1 main row/plot for destructive measurements). ETc was calculated from ETo (Penman–Monteith FAO) × Kc of chili per phase. The measured sample results showed that in the scheduled I80–M1–SPDI combination: a yield of 11.8 t ha⁻¹ with a total irrigation water of 3,900 m³ ha⁻¹, resulting in a WUE of 3.03 kg m⁻³ (+41% compared to I100–M0); post-harvest losses decreased by 23%, and quality scores (a* color value, flesh thickness) increased significantly (p<0.05). Financial analysis showed a B/C of 1.58 and a payback of 2.2 seasons when the solar system was depreciated over 8 years. The study confirmed that a 20% deficit in SPDI with organic mulch could shift the water efficiency–yield curve to the optimum zone without quality degradation, making it suitable for scenarios with limited water and fluctuating energy costs.